Social Relations and Local Community Adaptation to the Presence of Mining Corporations in Banyuwangi - Sudarsono; Bonaventura Ngw; Catur Wahyudi (Cita konsultindo, 2025)
This study aims to analyze the dynamics of social relations and forms of adaptation of local communities to the presence of the mining company PT. Bumi Suksesindo (PT BSI) in Sumberagung Village, Pesanggaran District, Banyuwangi Regency. The presence of the gold mining industry has significantly changed the social, economic, and cultural structure of the community. This study uses a qualitative approach with a case study method, through data collection techniques in the form of field observations, in-depth interviews with the community, company officials, and government officials, as well as documentation. Data analysis was conducted interactively through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the social relationship between the community and PT BSI is dynamic and complex, reflecting a process of negotiation between economic, social, and ecological interests. The community showed three main patterns of response to the presence of the mine: (1) cooperative, through involvement in corporate social responsibility (CSR) programs; (2) adaptive, by adjusting economic and social activities to changes in their living space; and (3) resistant, through rejection or criticism of the perceived environmental and social impacts. These patterns form a layered configuration of social relations between the community, the company, and the government, in which processes of accommodation and conflict occur simultaneously. This study concludes that the success of social relations between mining companies and local communities is highly dependent on two-way communication, policy transparency, and respect for the social values and local wisdom of the community. The implications of this study emphasize the importance of participatory social interaction models as the basis for equitable and sustainable community-corporate relationship management in mining areas